2022
DOI: 10.1111/lang.12526
|View full text |Cite
|
Sign up to set email alerts
|

Spacing Effects in Task Repetition Research

Abstract: This article provides a conceptual review of the principles of input spacing as they might relate specifically to oral task repetition research and presents some of the common methodological considerations from the broader input spacing literature. The specific considerations discussed include the interaction between intersession intervals and retention intervals, the manipulation of posttests as a between-participants variable, the number of task repetitions, absolute versus relative spacing, the criterion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 117 publications
1
6
0
Order By: Relevance
“…Although previous research has demonstrated the benefits of task repetition, little attention has been given to the issue of when to repeat the task (Rogers, 2023), especially within the domain of L2 fluency research. Bui et al (2019) were the first to conduct a study specifically examining the effects of task repetition schedule on L2 oral performance.…”
Section: The Role Of Practice Distribution In Fluency Developmentmentioning
confidence: 99%
“…Although previous research has demonstrated the benefits of task repetition, little attention has been given to the issue of when to repeat the task (Rogers, 2023), especially within the domain of L2 fluency research. Bui et al (2019) were the first to conduct a study specifically examining the effects of task repetition schedule on L2 oral performance.…”
Section: The Role Of Practice Distribution In Fluency Developmentmentioning
confidence: 99%
“…This could affect the number of sessions required to reach Stage 3. In contrast, longer intersession intervals may promote better retention of the declarative knowledge of rules (Bird, 2010; Nakata et al., 2023; for review, see Rogers, 2023). If so, learners might still have full access to their declarative knowledge at the posttest and thus would not need to reach Stage 3 in order to score highly.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In this methodological design, standard tasks measuring skill performance using standardized video stimuli depicting difficult video moments can be utilized [56]. Participants respond to a number of similar stimuli allowing for task repetition much like that seen in task repetition studies in second language learning [57]. Within subject task repetition designs can also minimize the risk of interpreting communicatively meaningful disfluencies as failures of speech thanks to the comparison with personal baselines.…”
Section: Experimental Studiesmentioning
confidence: 99%